Estudio sobre la enfermedad de Tyzzer (Clostridium piliforme) en diferentes cepas de ratas y ratones de laboratorio infectadas experimentalmente - Ayala, Miguel (2010)
Laboratory animals like alive biological reactive, must be genetically and microbiologically defined in order to obtain reliable results. The use of unhealthy animals in research leads to wrong results. Tyzzer's disease is caused by Clostridium piliforme and the susceptibility or resistance in different rats and mice strains was unknown. In this study, the resistance and susceptibility to Clostridium piliforme in different rats and mice strains of Argentina were evaluated by experimental infection. The microbial concentration which produces the disease but not death was established. The biological properties of Clostridium piliforme were confirmed and the antibodies protection given in animals inoculated with different concentrations of Clostridium piliforme was determined. It was noted that Clostridium piliforme is equally pathogenic for different rats and mice strains with some differences in the lesions found. It was determined that the dose of 2x105 and 2x106 microorganisms, which stimulated the production of antibodies against Tyzzer's disease, did not cause illness in inoculated animals but they were protected against lethal dose. For that reason dose of 2x105 and 2x106 microorganisms could be used to protect rats and mice in a colony.